Chronic alcohol-induced long-lasting working memory deficits are associated with altered histone H3K9 dimethylation in the prefrontal cortex - De Clerck, Mael; Manguin, Martin; Henkous, Nadia; d’Almeida, Marion N.; Beracochea, Daniel; Mons, Nicole (Frontiers in Behavioral Neuroscience, 2024)
Epigenetic modifications have emerged as key contributors to the enduring behavioral, molecular and epigenetic neuroadaptations during withdrawal from chronic alcohol exposure.In the present study, we investigated long-term effects of a 3-week abstinence period after 5 months of ethanol consumption on working memory (WM) on a T-maze and transcriptionally repressive histone H3 lysine 9 dimethylation (H3K9me 2 ) in the prefrontal cortex (PFC) of male C57BL/6 mice. Withdrawal mice displayed WM impairments along with reduced prefrontal H3K9me 2 levels, compared to water-drinking mice. The withdrawal-induced decrease of H3K9me 2 occurred concomitantly with increased level of permissive H3K9 acetylation (H3K9ac) in the PFC. Treatment with the GABA B agonist baclofen during alcohol fading and early withdrawal rescued withdrawal-related WM deficits and fully restored prefrontal H3K9me 2 and H3K9ac. Alcohol withdrawal induced brain region-specific changes of H3K9me 2 and H3K9ac after testing, with significant decreases of both histone marks in the dorsal hippocampus and no changes in the amygdala and dorsal striatum. Furthermore, the magnitude of H3K9me 2 in the PFC, but not the hippocampus, significantly and positively correlated with individual WM performances. No correlation was observed between H3K9ac and behavioral performance. Results also indicate that pre-testing intraperitoneal injection of UNC0642, a selective inhibitor of histone methyltransferase G9a responsible for H3K9me 2 , led to WM impairments in water-drinking and withdrawal-baclofen mice. Collectively, our results demonstrate that alcohol withdrawal induced brain-region specific alterations of H3K9me 2 and H3K9ac, an effect that persisted for at least three weeks after cessation of chronic alcohol intake. The findings suggest a role for long-lasting decreased H3K9me 2 specifically in the PFC in the persistent WM impairments related to alcohol withdrawal.